1999
DOI: 10.1093/intimm/11.3.333
|View full text |Cite
|
Sign up to set email alerts
|

CD14 transgenic mice expressing membrane and soluble forms: comparisons of levels of cytokines and lethalities in response to lipopolysaccharide between transgenic and non-transgenic mice

Abstract: Two different metallothionein promoter-mouse CD14 fusion genes were constructed. The membrane form of the CD14 fusion gene, designated M14M, contained the full-length CD14 cDNA sequence, whereas the soluble form of the fusion gene, designated M14S, was truncated to lack the sequence for the phosphatidylinositol-anchoring site. Expression of transgenic RNA in M14M and M14S mice on the basal diet was abundant in the liver. After maintenance with water containing ZnSO4 (50 mM) for 4 days, expression of transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…sCD14 can also transfer cell-bound LPS to plasma lipoproteins (78). The fact that survival rates in the lethal Shwartzman reaction induced by LPS were significantly higher in CD14 transgenic than in nontransgenic mice is compatible with this hypothesis (79).…”
Section: Discussionmentioning
confidence: 78%
“…sCD14 can also transfer cell-bound LPS to plasma lipoproteins (78). The fact that survival rates in the lethal Shwartzman reaction induced by LPS were significantly higher in CD14 transgenic than in nontransgenic mice is compatible with this hypothesis (79).…”
Section: Discussionmentioning
confidence: 78%
“…With respect to protection against LPS, the role of sCD14 is less established and has been addressed in several publications. Two independent groups generated transgenic mice expressing CD14 under control of either the Moloney murine leukemia virus long terminal repeat [10] or the metallothionein promoter [11] and reported an increase and decrease in sensitivity to LPS in vivo, respectively. To clarify this contradiction and to see if hCD14 is capable of complementing LPS signaling in mice in the absence of endogenous CD14, we generated transgenic mice using BAC DNA covering the CD14 locus and containing the genomic areas 40 kb upstream and downstream of the CD14 initiation transcription site.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a hCD14 transgene driven by a heterologous promoter is capable of protecting animals from the lethal effects of LPS [11]. Prior to that, a second group using a similar system found that transgenic mice are hypersensitive to LPS, thus providing an opposite effect and conflicting data [10].…”
Section: Cellular Responses To Lps In Hcd14-transgenic Micementioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mice overexpressing CD14 are more sensitive to LPS-induced shock than CD14-expressing controls (15,48), while mice deficient in CD14 (CD14 knockout [CD14KO] mice) show little or no response to a dose of LPS that is 10-fold higher than a 100% lethal dose for CD14-expressing mice (21). Furthermore, intraperitoneal or intravenous administration of a dose of Escherichia coli O111 that is lethal for control mice produces little or no response in CD14KO mice, indicating that CD14 mediates the LPS-induced state (21).…”
mentioning
confidence: 99%